Numerical and experimental estimation of void fraction of supersonic steam jet in sub-cooled water: a comparative study - Afrasyab, Khan; Spiridonov, Evgeny; Podzerko, Alexander; Darya, Khabarova; Mohammed, Zwawi; Mohammed, Algarni; Bahadar, Ali; Sanaullah, Khairuddin; Felemban, Bassem F.; Ullah, Atta; Andrew Ragai, Henry Rigit (IEEE, 2020)
Gas-liquid two-phase flows occur in a range of chemical, process, petroleum, metallurgical and power industries. Void fraction is a principal parameter. An effort has been made here to perform a comparative study in which the approximate void fraction of the supersonic steam jet into the sub-cooled water has been measured both numerically as well as experimentally. On a numerical basis, Direct Contact Condensation (DCC) model and on an experimental basis, Electrical Resistance Tomography (ERT) has been used for computing the void fraction. On an experimental basis, the overestimation is nearly 45% when the surrounding water temperature is 30°C with a steam inlet pressure of 1.5 bars and the over-estimation goes up to 83% at 60°C and 3.0 bars. The void fraction computed by the use of the DCC model at 1.5 bars and 300C is 17.66% whereas the computed void fraction at 3.0 bars of inlet pressure and 600C of water temperature is 31.1%.